The Complete Monterey Pop Festival - Hegedus, Chris 1952-; Hendrix, Jimi 1942-1970; Redding, Otis 1941-1967; Redding, Noel; Mitchell, Mitch 1946-2008 (Criterion Coll., 2002)
Documentary about Monterey Pop Festival of 1967; includes festival footage and performances.
Orig.: 1986. - Früheres Copyright 1987
Enth. audio commentary by music critic and historian Charles Shaar Murray ; Trailer ; video excerpt: Pete Townshend on Monterey and Jimi Hendrix
Keywords: Hendrix, Jimi -- 1942-1970; Monterey International Pop Festival -- (1967 : -- Monterey, Calif.); Documentary films; Music festivals; Music videos; Popular music -- 1961-1970; Rock music -- 1961-1970; DVD-Video